Response of yearling steers on bluestem pasture to Ralgro, Synovex S and Stilbestrol implants - Smith, E.F.; Riley, Jack G.; Boggs, Don (Kansas State University. Agricultural Experiment Station, 2011)
One hundred seventy-five Hereford, Hereford-Angus cross and Angus steers, averaging 553 lbs., were distributed as equally as possible by breed among four pastures. The pasture season was May 2 to October 5, 1975 (152 days). A third of the steers in each pasture were implanted with one of the three following materials: Ralgro, Synovex S, Stilbestrol (30 mg.). There was no significant difference in gains by the groups. Previous research has shown that Stilbestrol implants increase weight gains of steers on bluestem pasture 10 to 15 percent.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Yearling steers; Bluestem pasture; Implants